ANALYSIS OF INITIAL SUPPORT DESIGN OF SAMARINDA TUNNEL STA 0+425 USING H-BEAM WITH 3D MODELING - Abraham Tuwan, George
The Samarinda tunnel has a horseshoe geometry, egg-shaped with a 10.5 m vertical length and 12.8 horizontal length which will be excavated using the top and bench method. STA 0+425 (BH-04) is the deepest tunnel construction with a depth of 62 m and is in sandstone lithology. Therefore it is necessary to analyze the stability of the tunnel through the application of the initial support H-Beam using the initial support recommendation with the Terzaghi rock mass classification method, the QSystem, and the RMR with empirical and numerical calculations which will be modeled in 3D, then the results of the two will be compared. With the empirical results, it is found that the lowest factor of safety for each methods is 1.6 to 6.0 and with the recommendation 3D numerical results, it is found that the value of ?1 continues to increase from the initial condition which means that there is an arch effect so that there will be a redistribution of stresses in the tunnel structure. The largest vertical displacement value is 5.5 mm with a vertical strain value of 0.09% and the largest convergent horizontal displacement value is 0.5 mm with a horizontal strain value of 0.04%. The largest extrusion value in tunnel progress is 2.9 mm and the safety factor of the buffer is greater than 1.5. Thus, the application of the initial support from the optimization results is feasible to be applied to the construction of the Samarinda Tunnel.